Plant layout improvement for capacity balancing by problem modeling simulation technique in hard disk drive industry - Samanphan, Waewdao; Kantanantha, Nantachai (Engineering and Applied Science Research, 2014)
This research has an objective to propose the guideline of the plant layout improvement for the hard disk drive production process in the Clean Room area. The principle of the Systematic Layout Planning or SLP which is the layout planning process focusing on the relationship between stations is applied. This leads to shorter transfer distance and transfer time reduction. Currently, the Clean Room of the case study factory is divided into two parts, Phase 1 and Phase 2. Most of the production processes in both phases are similar but the capacities are different. This causes the imbalance problem of the capacities between Phase 1 and Phase 2 and results in many material transfers across the phases. Moreover, the work stations are located in disorder. Some work stations are far from each other which result in long transfer distance. This research proposes two improved plant layouts. The efficiency of the proposed layouts are evaluated and compared to the current one by simulation technique using Arena program. The simulation results show that, compared to the current layout, the improved plant layouts No.1 and No.2 reduce the transfer times by 14.32% and 22.58%, respectively, which lead to the annual saving of transportation costs by 432,000 baht and 648,000 baht, and reduce the required spaces in the Clean Room by 111 and 117 square meters, respectively.